Aerodrome Safety for Manouvering Area in Soekarno-Hatta International Airport Cengkareng - Ricardianto, Prasadja; Rifni, Muhammad; Prasetya, Oce (STMT Trisakti, 2015)
This research was conducted in the area of Soekarno-Hatta, Cengkareng. The purpose of this study is to determine the conformity between Soekarno-Hatta airport Aerodrome Safety For Manouvering Area and the Local Government Regulation of Tangerang City. The method used in this study is a survey method or field study and at the explanatorydescriptive level. The methods of data collection are documentation, interviews, and observation. The result of the study can be concluded through the role of the Tangerang City government in making the 2012-2023 spatial plan of Tangerang City, recommendations on Aerodrome Safety For Manouvering Area against the local government regulation on the building construction Tangerang City which have been made by the local government and the Regional Airport Authority I of Soekarno-Hatta Airport, and conclusions regarding the conformity between Soekarno-Hatta Airport Aerodrome Safety For Manouvering Area and Local Government Regulation of Tangerang City implemented in the Development Activity Plan of space structure plan consisting of the main activities of Soekarno-Hatta International Airport, Supporting Activities of Green Open Space, Land Use Plan. Keywords: Aerodrome Safety For Manouvering Area, Obstacle, Local Government Regulation